Reduction in length of transient region in successive forging of tailored blank for hot stamping of ultra-high strength steel parts. (2017) - Nakagawa, Yuki; Mori, Ken-ichiro; Murata, Yoshimitsu; Maeno, Tomoyoshi
Abstract: Tailored blanks having a thickness distribution without welds were produced by successive forging, and the length of the transient region in which the thickness gradually decreases was reduced by an infinitesimal feed. The effect of the infinitesimal feed on the reduction of the length of the transient region was evaluated. A tailored blank having a desired thickness was successive-forged, and was hot-stamped into a roof bow. The produced roof bow had sufficient hardness and high paintability.